KNOWLEDGE, AWARENESS, AND PROTECTIVE PRACTICES OFHEPATITIS B VIRUS AND INFECTION CONTROLMEASURES AMONGST DENTAL STUDENTS - Aneeqa Shahab; Aisha Wali; Naseem Ahmed Khan; Batool Fatima; Sidra Siddiqui (Baqai Journal of Health Sciences)
Objectives: The purpose of this study was to assess the knowledge, attitudes, and level of practice regarding infection control amongst dental students.